Optical amplifier number and placement in the suiperPON architecture - Sakena, A.J.; Jamro, M.Y; Senior, J.M. (IEEE, 2004)
Three alternative optically amplified long reach, wide splitting ratio PON (SuperPON) amplifier placement strategies (i.e architectural configurations) are modelled using the Virtual Photonic Integration (VPI) simulation package. In particular optical power budgetary analysis is carried out an three SuperPON dimensions of 1W km, 110 km and 130 km for the three configurations with the range of splitting ratios from 256 to 131,072 optical network units (ONUs). From the simulations the optimum placement and the minimum number of optical amplifiers required for SuperPON architecture is determined and graphical date Is discussed in relation to the different network sizes and dimensions. Using this approach it is demonstrated that a single amplifier is sufficient to provide for up to 1,024 ONUs and that this number Increase to six amplifiers with three in cascade to service 131,072 ONUs.